Automation of cellular therapy product manufacturing: results of a split validation comparing CD34 selection of peripheral blood stem cell apheresis product with a semi-manual vs. an automatic procedure. Issue 1 (December 2016) - Hümmer, Christiane; Poppe, Carolin; Bunos, Milica; Stock, Belinda; Wingenfeld, Eva; Huppert, Volker; Stuth, Juliane; Reck, Kristina; Essl, Mike; Seifried, Erhard; Bonig, Halvard
Abstract Background Automation of cell therapy manufacturing promises higher productivity of cell factories, more economical use of highly-trained (and costly) manufacturing staff, facilitation of processes requiring manufacturing steps at inconvenient hours, improved consistency of processing steps and other benefits. One of the most broadly disseminated engineered cell therapy products is immunomagnetically selected CD34+ hematopoietic "stem" cells (HSCs). Methods As the clinical GMP-compliant automat CliniMACS Prodigy is being programmed to perform ever more complex sequential manufacturing steps, we developed a CD34+ selection module for comparison with the standard semi-automatic CD34 "normal scale" selection process on CliniMACS Plus, applicable for 600 × 106 target cells out of 60 × 109 total cells. Three split-validation processings with healthy donor G-CSF-mobilized apheresis products were performed; feasibility, time consumption and product quality were assessed. Results All processes proceeded uneventfully. Prodigy runs took about 1 h longer than CliniMACS Plus runs, albeit with markedly less hands-on operator time and therefore also suitable for less experienced operators. Recovery of target cells was the same for both technologies. Although impurities, specifically T- and B-cells, were 5 ± 1.6-fold and 4 ± 0.4-fold higher in the Prodigy products (p = ns and p = 0.013 for T and B cell depletion, respectively), T cell contents per kg of a virtual recipient receiving 4 × 106 CD34+ cells/kg was below 10 × 103 /kg even in the worst Prodigy product and thus more than fivefold below the specification of CD34+ selected mismatched-donor stem cell products. The products' theoretical clinical usability is thus confirmed. Conclusions This split validation exercise of a relatively short and simple process exemplifies the potential of automatic cell manufacturing. Automation will further gain in attractiveness when applied to more complex processes, requiring frequent interventions or handling at unfavourable working hours, such as re-targeting of T-cells.